INTEGRATION OF ECONOMIC AND COMPUTER SKILLS AT IMPLEMENTATION OF STUDENTS PROJECT «BUSINESS PLAN PRODUCING IN MICROSOFT WORD» - Samchinska Я.Б. (Journal of Information Technologies in Education (ITE), 2012)
In the article expedience at implementation of economic specialities by complex students project on Informatics and Computer Sciences is grounded on creation of business plan by modern information technologies, and also methodical recommendations are presented on implementation of this project.